The Interaction of Water Suspension Incarbonic Dolomite with Sulfuric Acid and Carbon Dioxide - Duda, O.M.; Kostiv, I.J. (Physics and Chemistry of Solid State, 2016)
The interaction of aqueous suspension of calcium chloride has been studied at different temperatures and at the duration of natural dolomite and solutions of sulfate acid and also carbon dioxide. Studied composition of formed products. Established that the reaction rate of magnesium oxide with acid or carbon dioxide is lower than calcium oxide. The conditions of obtaining of active magnesium with content ballast calcium carbonate and sulfate, which is connected to soluble calcium. For 1023 K temperature forms the most active magnesium oxide, increasing it to 1123 K, magnesium oxide is passivated and increasing the number of active calcium oxide. Soluble calcium compound completely pass into insoluble sulfates or carbonates by passing through a suspension of carbon dioxide or solution of sulfate acid neutralization. Thermo activated dolomite which containing active magnesium oxide and various forms of inert material can be used for obtaining magnesia binders.